Student Perceptions: The Use of Artificial Intelligence in Online Assignments at Affordable Universities in Jakarta, Indonesia. - Rachman, Izmirta; Donald, Eriklex (PT ARRUS Intelektual Indonesia, 2025)
Artificial Intelligence (AI) has become necessary for students to complete online assignments, which threatens the creativity and originality of student thinking. This study explores the background, frequency, and strategies of AI usage from the perspective of management study program students at affordable universities. The qualitative results show that all students use AI with very high frequency. Students consider using AI for (1) practicality, (2) speed, (3) accuracy, and (4) information sources. Students have become wise and intelligent in using AI and hope for the legitimacy of AI as an assistive tool. Students do not feel guilty about using AI as long as they do not engage in full plagiarism and cite other information sources beyond AI. The formation of a new paradigm or sub-paradigm is highly recommended, where AI is encouraged as a reference source and the learner as a quote. Further research development is suggested to use quantitative methods to examine the relationship between practicality, speed, accuracy, and information source on students' assignment outcomes using AI. It is also highly recommended to conduct further research on whether AI can be considered an official citation source and to make AI an official assistive tool for students at affordable universities.